Network Reconfiguration of 20 kV Sample Connection Substance LG-04 Lhokseumawe City Using Digsilent Power Factory Software Simulation 15.1 - Arnawan Hasibuan; Kartika Kartika; Sahal Mahfudz; Muhammad Daud (International Journal of Advances in Data and Information Systems, 2022)
In this final project, we describe the study of reconfiguring the distribution network at the LG-04 feeder at the Lancang Garam substation, Lhokseumawe, to improve the performance of the distribution system. The focus of the parameters considered includes continuity, voltage, and power loss. The reconfiguration is to change the initial network topology which is in the form of radial into a loop. After reconfiguration, the calculation of power flow, voltage drop, power loss, and short circuit calculation is also carried out which becomes a reference for whether or not the quality of the network is good. The results of the simulation of the existing conditions show that continuity is not good, after reconfiguration and fault testing, the network does not experience blackouts like the network before reconfiguration. The power loss generated in the network after reconfiguration is 0.507 kW or a decrease of ±84% from the previous form of the network.